The Tourtous Course and Branching Pattern of Ulnar Artery Around Guyon’s Canal - Nazia Quadir; Rashmi Deopujari; Ranjana Agrawal; Ashwini Kudopa; Rajveer Singh Chourasia (Journal of Pharmacy and Bioallied Sciences)
Background: The ulnar artery, the larger terminal branch of the brachial artery, is a key contributor to forearm vascularization. It traverses the Guyon’s canal alongside the ulnar nerve in the palmar medial carpal region. Due to its favorable anatomical properties, the ulnar artery has gained significance as an alternative to the radial artery for coronary angiography and angioplasty. Additionally, the ulnar artery forearm flap is widely used in reconstructive head and neck surgeries and post-burn contracture management. Variations in the course and branching pattern of the ulnar artery in the medial carpal region are clinically significant for surgical interventions. Materials and Methods: The study was conducted on 50 formalin-fixed cadaveric upper limbs obtained from the Department of Anatomy, P.C.M.S. and R.C, Gandhi Medical College, and Chirayu Medical College. Dissection was performed in the medial palmar carpal region to examine the course, tortuosity, and branching pattern of the ulnar artery. The boundaries of the Guyon’s canal were delineated, and any variations in the artery’s trajectory and termination were recorded. Digital photographs documented the anatomical findings. Results: In all but one case, the ulnar artery was found to traverse through the Guyon’s canal. A tortuous course was observed in 38% of cases, while 62% exhibited a straight trajectory. The tortuosity extended 6 cm proximally and 4 cm distally from the pisiform bone and resulted in ulnar nerve kinking in 16% of cases. The deep terminal branch originated distal to the pisiform in 94%, at its level in 4%, and proximal to the pisiform in 2% of cases. The artery was accompanied by venae comitantes and gave rise to dorsal cutaneous, dorsal carpal, and palmar carpal branches. A unique case was noted where the deep branch traversed deep to the flexor retinaculum and gave off a superficial branch entering the palm. Conclusion: This study highlights the variability in the ulnar artery’s course, with a 38% prevalence of tortuosity and its potential impact on clinical procedures. The findings are crucial for vascular surgeons and interventional cardiologists, especially when performing transulnar angiography and angioplasty. Additionally, understanding the branching pattern enhances precision in reconstructive microsurgery and prevents inadvertent nerve compression or ischemic complications.